Reconstruction formula for the potential function of Sturm-Liouville problem with eigenparameter boundary condition - Panakhov, Etibar S.; Koyunbakan, Hikmet; Ic, Unal (Taylor & Francis Ltd, 2010)
It is known that the uniqueness of potential function of the Sturm-Liouville problem can be shown from the nodal points. In this article, we solve the inverse nodal problem of the reconstruction of the potential function q from the nodal data by a pointwise limit. We show that this convergence is in the L-1. It is mentioned that this method is based on the works of Law and Yang, but we have applied the method for the Sturm-Liouville problem depending on eigenparameter boundary conditions.
4th International Conference on Inverse Problems - Modeling and Simulation -- MAY 26-30, 2008 -- Fethiye, TURKEY
Keywords: Sturm-Liouville problem; nodal points; reconstruction formula